Measurement, Determinants, and Implications of Energy Intake in Athletes - Holtzman, Bryan (Nutrients, 2019)
Appropriate energy intake is important for the health and performance of athletes. When an athlete’s energy intake is not concordant with energy expenditure, short- and long-term performance can be compromised and negative health effects may arise. The energy intake patterns of athletes are subject to numerous effectors, including exercise response, time, and availability of food. To assess different determinants of energy intake in athletes, we reviewed recent literature regarding the response of appetite-regulating hormones to exercise, appetite perceptions following exercise, chronic exercise-induced adaptations regarding appetite, and social factors regarding energy intake. Additionally, we discussed consequences of aberrant energy intake. The purpose of this review is to clarify understanding about energy intake in athletes and provide insights into methods toward maintaining proper energy intake.